Effect of Maternal Administration of Edible Bird’s Nest on the Learning and Memory Abilities of Suckling Offspring in Mice - Yong Xie; Hongliang Zeng; Zhiji Huang; Hui Xu; Qunyan Fan; Yi Zhang; Baodong Zheng (Neural Plasticity)
Although human brains continue developing throughout the underage developmental stages, the infancy period is considered the most important one for the whole life. It has been reported that sialic acid from edible bird’s nest (EBN) can facilitate the development of brain and intelligence. In this study, by oral administration of EBN to female mice during the pregnancy or lactation period, the effects of EBN on the levels of sialic acid in mouse milk were determined using high-performance liquid chromatography (HPLC). Furthermore, the spatial learning performances of their offspring were assessed using the Morris water maze test. Additionally, cerebral malondialdehyde (MDA), superoxide dismutase (SOD), choline acetyltransferase (ChAT), and acetylcholinesterase (AChE) in cubs nursed by the female mice given the EBN homogenate were examined, while BDNF immunohistochemical staining and neuron count in hippocampi were investigated as well. These results showed that administration with EBN in maternal mice during pregnancy or lactation period can improve the learning and memory functions in their offspring, possibly by increasing the activities of SOD and ChAT and, at the meantime, decreasing the levels of MDA and activities of AChE. Moreover, BDNF levels for CA1, CA2, and CA3 regions in hippocampi and the numbers of dyed neurons in CA1, CA2, CA3, and DG regions among the offspring were significantly enhanced due to the intake of EBN by the maternal mice. We concluded that maternal administration of EBN during the pregnancy and lactation periods can improve the spatial learning performances in the offspring.